Microbiologia e histopatologia de pododermatite em frangos de corte após escarificação epidérmica - Giron, Talita Vitória (2014)
The objective of this study was to evaluate microbiological and histopathological effects of using foot ulcers remover machine in varying degrees of foot pad dermatitis in broilers. The injured and uninjured legs were collected in a poultry slaughterhouse and separated by degrees of foot ulcers. Grades were defined according to the compromised ratio existing in the plantar surface macroscopically visible: 0 - no lesion, 1 - less than 25% damage, 2 - injury between 25 and 50% and 3 - more than 50%. Following selection of 60 feet each type, 30 samples went through the process of the foot ulcer removal using the machine. All samples were evaluated histopathologically and microbiologically totaling 240 experimental units. Inside the microbiological evaluation, swabs from the footpads of the samples were collected and from these seven successive dilutions were performed, sown on plates for counting of mesophilic aerobic and total coliforms with differentiation for Escherichia coli and incubated in chamber (B.O.D. type) emissions at 35 °C for 48 hours to count. For histopathological analysis, the samples were fixed in 10% buffered formalin for approximately 24 hours and submitted to three sections of each footpad: top (next to the digits), central and bottom. The resulting fragments were processed to derive the blades evaluated in accordance with the presence and quantification of inflammatory infiltrate. Data were analyzed using the F test and submitted to Tukey test to compare averages. The samples which underwent the removal procedure showed better results when compared with samples that have not undergone the procedure and even better than samples with no macroscopically evidence of foot pad dermatitis, demonstrating the effectiveness of the equipment in the lesions removal. Microbiological analyzes showed no correlation with pododermatite scores evaluated.Presence of microbiological contamination exceeding the acceptable levels in accordance with the standards established by Brazilian law were not detected in the analyzed products under the conditions studied, indicating good hygiene and product safety